Development and validation of primary human myometrial cell culture models to study pregnancy and labour - Mosher Andrea A; Rainey Kelly J; Bolstad Seunghwa S; Lye Stephen J; Mitchell Bryan F; Olson David M; Wood Stephen L; Slater Donna M (BMC, 2013)
Abstract Background The development of the in vitro cell culture model has greatly facilitated the ability to study gene expression and regulation within human tissues. Within the human uterus, the upper (fundal) segment and the lower segment may provide distinct functions throughout pregnancy and during labour. We have established primary cultured human myometrial cells, isolated from both upper and lower segment regions of the pregnant human uterus, and validated them for the purpose of studying human pregnancy and labour. The specific objectives of this study were to monitor the viability and characterize the expression profile using selected cellular, contractile and pregnancy associated markers in the primary cultured human myometrial cells. Labour has been described as an inflammatory process; therefore, the ability of these cells to respond to an inflammatory stimulus was also investigated. Methods Myometrial cells isolated from paired upper segment (US) and lower segment (LS) biopsies, obtained from women undergoing Caesarean section deliveries at term prior to the onset of labour, were used to identify expression of; α smooth muscle actin, calponin, caldesmon, connexin 43, cyclo-oxygenase-2 (COX-2), oxytocin receptor, tropomyosin and vimentin, by RT-PCR and/or immunocytochemistry. Interleukin (IL)-1β was used to treat cells, subsequently expression of COX-2 mRNA and release of interleukin-8 (CXCL8), were measured. ANOVA followed by Bonferroni's multiple comparisons test was performed. Results We demonstrate that US and LS human myometrial cells stably express all markers examined to at least passage ten (p10). Connexin 43, COX-2 and vimentin mRNA expression were significantly higher in LS cells compared to US cells. Both cell populations respond to IL-1β, demonstrated by a robust release of CXCL8 and increased expression of COX-2 mRNA from passage one (p1) through to p10. Conclusions Isolated primary myometrial cells maintain expression of smooth muscle and pregnancy-associated markers and retain their ability to respond to an inflammatory stimulus. These distinct myometrial cell models will provide a useful tool to investigate mechanisms underlying the process of human labour and the concept of functional regionalization of the pregnant uterus.